Obesity in Gynecologic Oncology - Kölbl, Heinz; Bartl, Thomas (Geburtshilfe und Frauenheilkunde, 2020)
Abstract The decades-long global obesity epidemic has resulted in steady increase in the incidence of obesity-related malignancies. The associated diagnostic and therapeutic implications present a clinical challenge for gynecologic oncology treatment strategies. Recent studies have provided solid evidence for an independent, linear, positive correlation between a pathologically increased body mass index and the probability of developing endometrial or postmenopausal breast cancer. The pathogenesis is complex and the subject of current research. Proposed causes include pathologically increased serum levels of sexual steroids and adiponectin, obesity-induced insulin resistance, and systemic inflammatory processes. The scientific evidence for an association between obesity and other gynecological malignancies is, however, less solid. The clinical relevance of obesity as a risk factor for epithelial ovarian cancer, cervical cancer and vulvar cancer appears to be negligible. Nevertheless, obesity appears to have a negative impact on prognosis and oncologic outcomes for all gynecological cancers. Whether or not this effect can be interpreted as correlative or causal is still a subject of ongoing debate. Zusammenfassung Als Folge der weltweit seit Jahrzehnten ansteigenden Adipositasprävalenz stellen die zunehmende Anzahl an Neudiagnosen adipositasassoziierter Malignome und damit einhergehende diagnostische und therapeutische Implikationen gynäkoonkologische Behandlungsstrategien vor eine Herausforderung. Im Spiegel der aktuellen Studienlage besteht solide Evidenz für eine unabhängige, linear positive Korrelation zwischen einem pathologisch erhöhten Body-Mass-Index und der Erkrankungswahrscheinlichkeit für Endometrium- und postmenopausale Mammakarzinome. Die Pathogenese ist komplex und Gegenstand intensiver Forschung, pathologisch erhöhte Serumspiegel von Sexualsteroiden und Adiponektinen, eine adipositasinduzierte Insulinresistenz sowie systemische Inflammationsprozesse werden als ursächlich diskutiert. Für andere gynäkologische Malignome zeigt sich die wissenschaftliche Evidenz weniger solide, Adipositas erscheint als Risikofaktor für epitheliale Ovarial,- Zervix und Vulvakarzinome von vergleichsweise untergeordneter klinischer Relevanz. Ein negativer Einfluss auf die Prognose und das onkologische Outcome zeigt sich hingegen für alle Tumorentitäten nachvollziehbar, wobei eine abschließende Bewertung, ob dieser Effekt korrelativ oder kausal zu interpretieren ist, weiterhin aussteht.